THE STRATEGIES IN TEACHING SPEAKING AT UNIVERSITY OF PGRI PALEMBANG - Marleni, Marleni (English Community Journal, 2019)
Speaking as one of the four skills in English is seen as the most crucial skill to be mastered by English learners. For most people the successes in learning a language can be seen from how far the student can speak and communicate in the language learn. But in fact, speaking is often neglected in the classroom. The objective of this research is to investigate strategies in teaching speaking skill in second semester of English Department of University of PGRI Palembang. This study employs the qualitative design by which the researcher intends to discover and understand strategies of teaching speaking used by the lecture in its natural setting. The subject of this research was second semester students of English department. This study reveals four strategies employed by the lecturer in teaching speaking skill, i.e. show-and-tell, presentation, drama making, and question and answer. Show-and-tell and presentation strategy are two types of performance talk which were used more often by the lecturer than the two other strategies (i.e. drama making and question and answer).